A study of perinatal outcome in patients with breech presentation at tertiary care centre - Jadhav, Rajitha; Yadav, Babli; Kumar, Kranthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Regardless of the delivery method, breech presentation causes a 2–4 times increase in perinatal death and morbidity. Any change toward the method or technique of breech birth should attempt to enhance the perinatal result as well as maintain low rates of maternal morbidity and mortality. The success of a particular strategy for the management of labour with breech presentation is determined by the fetal outcome. Methods: This prospective observational study was conducted in 320 consecutive patients with breech presentation at tertiary care centre from 1 January 2021 to 31 August 2022. This study was approved from Institutional ethical committee. Results: In 206 primi gravida females, 4 underwent vaginal breech delivery and 202 had LSCS. Among 114 multigravida females, 66 had LSCS and 48 had vaginal breech delivery. Majority (213 cases, 66.6%) were term deliveries and 33.4% (107 cases) had preterm deliveries. 83.38% (268 cases) had LSCS and 16.3% (52 cases) had vaginal delivery. Of all vaginal deliveries 46 were assisted vaginal deliveries and 6 were spontaneous vaginal delivery. It was found that out of all 52 vaginal deliveries, 15 (28.8%) patients had complications. And out of all 268 LSCS, 32 (11.9%) patients had complications. Maternal complications were found to be statistically significant associated with vaginal breech delivery (p=0.02*). Total 5 perinatal mortalities were observed with emergency LSCS and no perinatal mortality was found with elective LSCS. Conclusions: Multiparous women has better maternal and perinatal outcome compared to Primigravida with breech presentation. Zero perinatal mortality in elective caesarean section. Perinatal outcome is good in elective LSCS than in an emergency LSCS.